2020
DOI: 10.1002/ijc.33185
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of anal cancer incidence by risk group: Toward a unified anal cancer risk scale

Abstract: Certain population groups are known to have higher than average anal cancer risk, namely persons living with HIV (PLHIV), men who have sex with men (MSM), women diagnosed with human papillomavirus (HPV)-related gynecological precancerous lesions or cancer, solid organ transplant recipients (SOTRs) and patients with autoimmune diseases. Our aim was to provide robust and comparable estimates of anal cancer burden across these groups. Summary incidence rates (IRs), as cases per 100 000 person-years (py), were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
333
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(350 citation statements)
references
References 50 publications
8
333
1
8
Order By: Relevance
“…Vulval squamous cell carcinoma incidence has also been increasing, especially in younger women [ 25 ]. A recent meta-analysis [ 26 ] had shown that women with vulval cancer are one of the highest risk groups for anal cancer, with an incidence rate (IR) of 48 per 100 000 person years. For women with cervical cancer and vaginal cancer the anal cancer risk was lower than for the vulva, but also with a high incidence, with an IR of 9 per 100 000 persons year for the cervix and 10 per 100 000 persons year for the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Vulval squamous cell carcinoma incidence has also been increasing, especially in younger women [ 25 ]. A recent meta-analysis [ 26 ] had shown that women with vulval cancer are one of the highest risk groups for anal cancer, with an incidence rate (IR) of 48 per 100 000 person years. For women with cervical cancer and vaginal cancer the anal cancer risk was lower than for the vulva, but also with a high incidence, with an IR of 9 per 100 000 persons year for the cervix and 10 per 100 000 persons year for the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] HIV-positive (HIV+) men who have sex with men (MSM) have the highest incidence rates (85 per 100,000), followed by HIV+ men who have sex with women (32 per 100,000), and HIV+ women (22 per 100,000). [3] Besides the role of HIV, iatrogenic systemic immunosuppression e.g. for solid organ transplantation or autoimmune diseases (including Inflammatory Bowel Diseases (IBD), in particular Crohn's disease, or haematological malignancies) also increases the risk for anal cancer (up to 12 per 100,000).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-negative MSM (19 per 100,000) and women with prior human papillomavirus (HPV)induced (pre-)cancer also have substantially higher incidence rates (cervical: 6-9 per 100,000 and vulvar: 42-48 per 100,000). [3] Almost all anal cancers are squamous cell carcinoma (SCC) and are, similar to cervical cancer, mainly caused by a persistent high-risk (hr)HPV infection and preceded by precursor lesions: anal intraepithelial neoplasia (AIN; graded 1-3). [4] High-grade AIN (HGAIN; AIN2-3), also called anal high-grade squamous intraepithelial lesions (HSIL), can progress to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the USA, incidence of and mortality from SCCA has increased in recent decades, 2 and is now a common cancer among sexual minority men (SMM) especially HIV-positive SMM among whom incidence is 40-fold to 50-fold higher than in persons overall. [3][4][5] Since it will be decades before the benefits of HPV vaccines are fully realised, 6 screening for anal precancers and invasive disease is needed.…”
Section: Introductionmentioning
confidence: 99%